ATELIÊ: UMA PERSPECTIVA PARA REPENSAR OS TEMPOS, OS ESPAÇOS E A ATIVIDADE DOCENTE NA EDUCAÇÃO INFANTIL - Rodrigues, Paula Adriana (2019)
This study had as its theme of discussion to analyze the impacts that the continued formation on workshops may make possible to the teachers and managers of a municipal kindergarten of Santa Maria. To this end, the following specific objectives were listed: to investigate how the pedagogical work in the early childhood education of the school is developed, to identify the conceptions of teachers and managers about the dynamics of the atelier in early childhood education, to propose continuing education meetings in the school on the theme. from the studio. The collaborating subjects of this study were five (5) teachers and one (1) managing teacher who exercises the position of pedagogical coordinator of the researched institution. the methodology is a qualitative approach of the case study type. Data analysis was performed using Bardin's Content Analysis (2011) and the instruments used were the semi-structured interview. The results showed that the continuing education studies about the studios contributed to guide new work paths and studies in the school context of the researched institution. In summary, it is highlighted that the training of teachers and managers took place in the construction of a global school project in which teachers and management worked collectively on behalf of the main actors, the children. n addition, teachers have put themselves in an attitude of constant training, stressing that they are never definitively trained. The teaching activity in early childhood education is done and redo daily with the emergence of new challenges, in which teachers assume themselves as subjects of their practice actively positioning themselves in the decision-making of pedagogical work. Therefore, there is a need for the appreciation of the preschool professionals because they seek daily life, a challenge that requires tireless studies, the resumption of work and the search for improvement. Being the proposal of the studio an innovative and potentializing possibility of multiple languages of children and thus contributes to the qualification of teaching activity in early childhood education.